dramatic function and details of the relationship between text and presentation (Desdemona's play as a model) (Journal of the College of Basic Education, 2022)
The research tackles the most important issue in function of ( dramaturge ) and its problems between text and the show . it is an issue inwhich Arab and global theater is suffering about the personification of the dramaturgical and merge with the innovative achievement and the theatrical functions.While the Germans were able to stress the independence of the dramaturge as a function that lies between the function of the author and that of the director, as a third sensitive eye that is concerned with the aesthetic and intellectual observation for the work to create a balancebetween the text and the show without the occurrence of unbalances here or there. The research tackled the stage of development of this function passing through the author-dramaturge relation to the director-dramaturgerelation reaching to the independence diagnosis of the dramaturgicalfunction and its tasks and duties within the mechanism of dramatic show